Kaplun P. V., Honchar V.A., Tiutiunyk B.I., Matviishyn P.V. Investigation of the durability of steelsin corrosive - abrasive environments after hardening by ionic nitriding. - Каплун, П.В.; Гончар, В.А.; Тютюник, Б.І.; Матвіїшин, П.В. (Problems of Tribology, 2017)
Experimental study of the properties of the surface layer of steels after ion nitriding among the mixture of nitrogen and argon in their different ratios for different technological regimes. Investigated thickness, hardness, wear resistance and phase composition of the nitrided layers. On the basis of the plan of experiments investigated the analytical properties depending on the technological parameters of the process of ion nitriding. Constructed graphic dependence of the nitrided layer hardness of the surface of the technological parameters of the process of ion nitriding. The kinetics of the process of wear of the nitrided layers in the model abrasive solution. An optimization study properties of the nitrided layer by setting the maximum hardness of the surface, the thickness of the hardened layer and its durability. Found optimum conditions of ion nitriding steels for each of the studied characteristics. Key words: wear, ion nitriding, durability, steel.